Registro eletrônico em saúde: proposta de um modelo de informação para uso na atenção primária com vistas à interoperabilidade - Braga, Renata Dutra (2014)
There are various health information systems in use in the country, which serve different purposes, but are not interoperable. To ensure interoperability in the development of a model that serves different health professions was held this research, which aimed to define a conceptual model for the registration of health information in primary care. Methods: This action research with analytical approach was held in conjunction with a panel of experts to represent the health professions recognized by the National Health Council (CNS), which through discussion meetings identified and systematized essential information needed to evaluate the overall health of individual, in the context of multidisciplinary primary care demands generating a preliminary model. This model was validated by Delphi method and a consensus model was proposed. Results: The conceptual model to health information registration obtained goes beyond the demands of administration, since its focus is the individual - source of all the information that generates health demands. The central structure of the information registry model comprised four groups of information, which were called pillars: Data Gathering, Diagnosis, Care Plan and Evaluation. Each of these pillars presented subgroups important to the different professions, whose complexity limit of detail of information stood on the complexity of primary health care. Conclusion: This study represents a joint effort to establish an architecture of essential information for creating an electronic record in interoperable and necessary to meet the individual's health in primary care.